Easter Island archaeology : a tribute to Daniel Schávelzon on the 30th anniversary of the Center for Urban Archaeology at the University of Buenos Aires = Arqueologia en Rapa Nui (Isla de Pascua) : homenaje a Daniel Schávelzon a los treinta años del Centro de Arqueología Urbana de la Universidad de Buenos Aires - Schávelzon, Daniel (Access archaeology., 2016)
This well illustrated volume presents in its introduction a personal history of Daniel Schávelzon's experience of Easter Island during his youth before collecting all the papers and work he produced in 2014 leading up to his retirement.